L’ontologie des plantes dans l’Ovide moralisé. Métamorphoses et jeux d’interférence entre les règnes - Valentine Eugène (Studia Romanica Posnaniensia, 2025)
In L’Ovide moralisé, the Christianised medieval adaptation of Ovid’s Metamorphoses, the theme of metamorphosis provides a privileged observatory for probing the complex links between man and the plant world in the 14th century. Numerous stories highlight the way in which the medieval ontological system, broadly defined as analogist, can be permeated by animistic tensions. To shed light on this principle of hybridisation, this article will draw on Philippe Descola’s categories. Focusing on the author’s writing strategies and their effect(s), it will examine the principles of continuity and discontinuity between interiority and physicality. At the same time, by comparing the source text and its rewriting, we will be looking at possible changes in the way plants are perceived between Antiquity and the end of the Middle Ages.